Menuju Aparatur Sipil Negara ASN Bertaraf Intenasional - Rofik Fauzan (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of writing this paper is to discuss efforts towards achieving international standard State Civil Service (ASN) status. The quality and capabilities of ASN are very important to achieve national development goals, because ASN is an important component in carrying out government functions and providing public services. In the era of globalization and global competition, increasing ASN competency is a demand that cannot be ignored. This research explores the challenges and opportunities faced in creating international standard ASN. One of the things that will be discussed is the importance of training and education to improve ASN capabilities; use of ICT to improve public administration performance; and the importance of ethics and integrity in ASN work. In addition, this paper will present several case studies from countries that have succeeded in achieving high achievements in developing international standard ASN. By comparing the various strategies and approaches that have been implemented, this paper will present recommendations and guidelines for other countries wishing to improve the quality and credibility of their ASN. This research uses qualitative descriptive analysis with literature analysis and case studies. Relevant data is collected from reliable sources, including scientific journals, government reports, and current academic publications. The research results show that achieving international ASN status requires synergy between various parties, including government, academics and the private sector. Changes are needed in the ASN education and training system, with an emphasis on developing competencies that are relevant to global demands. Apart from that, ASN's competitiveness in facing the digital era will be strengthened by the intelligent and sustainable application of information and communication technology. However, the process towards international standard ASN must also be accompanied by the application of high ethics and integrity at all levels of government organizations. An attitude of integrity and professionalism will shape public trust in ASN and strengthen its position as an important pillar in the implementation of transparent and accountable government, such as in the implementation of e-government. This paper increases understanding of the strategies and actions that can be taken to achieve international standard ASN. It is hoped that improving the quality of ASN will increase government effectiveness and increase public satisfaction with good public services.